2010
DOI: 10.1007/s11030-010-9280-3
|View full text |Cite
|
Sign up to set email alerts
|

First computational chemistry multi-target model for anti-Alzheimer, anti-parasitic, anti-fungi, and anti-bacterial activity of GSK-3 inhibitors in vitro, in vivo, and in different cellular lines

Abstract: In the work described here, we developed the first multi-target quantitative structure-activity relationship (QSAR) model able to predict the results of 42 different experimental tests for GSK-3 inhibitors with heterogeneous structural patterns. GSK-3β inhibitors are interesting candidates for developing anti-Alzheimer compounds. GSK-3β are also of interest as anti-parasitic compounds active against Plasmodium falciparum, Trypanosoma brucei, and Leishmania donovani; the causative agents for Malaria, African Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…47 Thus, in numerous fields of research in drug discovery, various works have reported the development of advanced chemoinformatic models inspired by the idea regarding the calculation of Box-Jenkins moving averages. [33][34][35][36][48][49][50][51][52][53][54][55][56][57][58] In the first step, the following equation is employed: In Eq. 3, n(c r ) represents the number of peptides assayed by considering the same element of the experimental condition (ontology) c r , which have also been annotated as positive.…”
Section: Box-jenkins Moving Averages and Generation Of The Mtk-computmentioning
confidence: 99%
“…47 Thus, in numerous fields of research in drug discovery, various works have reported the development of advanced chemoinformatic models inspired by the idea regarding the calculation of Box-Jenkins moving averages. [33][34][35][36][48][49][50][51][52][53][54][55][56][57][58] In the first step, the following equation is employed: In Eq. 3, n(c r ) represents the number of peptides assayed by considering the same element of the experimental condition (ontology) c r , which have also been annotated as positive.…”
Section: Box-jenkins Moving Averages and Generation Of The Mtk-computmentioning
confidence: 99%
“…Additional non-MIFderived descriptors were generated to create a total of 128 descriptors. Volsurf descriptors have been previously used to predict antileishmanial activity of natural products on enzymes and predict activity of some molecules [17][18]. In a two-class classification, when a variable that is being investigated cannot be distinguished between the two groups (i.e., when there is no difference between the two distributions), the area under the ROC curve equals 0.5, which is to say that the ROC curve will coincide with the diagonal.…”
Section: Volsurf Descriptorsmentioning
confidence: 99%
“…Many studies have been realized for search of new GSK-3β inhibitors by applying LBDD [39,[61][62][63][64][65][66][67][68][69][70]. The most promising work in this area is related with the first computational chemistry mt-QSAR model for anti-AD, antiparasitic, anti-fungi, and anti-bacterial activity of GSK-3 inhibitors [39]. In that study, the first mt-QSAR model able to predict the results of 42 different experimental tests for GSK-3 inhibitors with heterogeneous structural patterns has been developed.…”
Section: Glycogen Synthase Kinase-3β (Gsk-3β)mentioning
confidence: 99%
“…Collectively, such methodologies have been able to provide the set up and detection of new drug candidates, optimizing time and resources. The use of QSAR methodologies have achieved considerable proportions, ranging from the analysis of homogeneous families of compounds [30][31][32], the screening of large heterogeneous database of molecules [33][34][35], to the simultaneous classification of different pharmacological profiles [36][37][38][39] and biological functions of proteins [40][41][42], including the use of complex networks theory (CNT) [43][44][45][46] and establishment of powerful web servers for drugs and target discovery [47][48][49][50]. The present work is focused on the role of the LBDD including QSAR methodologies pertaining to the design of new target inhibitors for anti-AD therapy.…”
Section: Introductionmentioning
confidence: 99%